Science and technology: Friends or enemies of women? - Sim, Cecilia Ng Choo; Hensman, Rohini (Journal of Gender Studies)
Looks at how little science and technology have affected the lives of millions of women and children worldwide, with emphasis on the number of women in Asia, Africa and Latin American who live in absolute poverty. Problems which women in these countries are faced with; How scientific and technological `progress' has resulted in depriving women of control over their lives; Detailed information on the impact of science and technology on women in these countries.